El rol del trabajador social según la concepción empresarial del autor García Del Junco - Chevez Roque, Nicole Ibeth (My University, 2021)
This paper refers to the importance of the social worker in the business sphere that is related to different processes that occurred during the 20th century, where different approaches emerge as welfare benefit, paramedic philanthropy, aseptic social service, demographic, adjustment, integration, revolutionary, mobilization, awareness that all intrinsically linked to its development constitute social work as an alternative in the labor field. The role of the social worker in business management is an entity that, through the organization of human, material, technical and financial elements provides goods or services, in exchange for a price that recognizes the replenishment of the resources used, resulting in the achievement of objectives desired by the employer for the proper development of activities within the company. Social worker exercises different functions, among the main ones can highlight the diagnosis, planning, guidance and advice to workers in the field of employment and human resources, ensuring that rights are not violated acquiring individual or collective working well-being that is very important in a functional or business community to which it belongs, with active and moderating participation of belonging to the company.
El presente trabajo trata de la importancia del trabajador social en el ámbito empresarial que está relacionada por diferentes procesos ocurridos durante el Siglo XX, donde surgen diversos enfoques como benéfico asistencial, el servicio social aséptico, demográfico, ajuste, integración, revolucionaria, movilización, concientización, todas unidas intrínsecamente a su desarrollo constituyen al Trabajo Social como una alternativa en el campo laboral. El rol del trabajador social en gestión empresarial es una entidad que, a través de la organización de elementos humanos, materiales, técnicos y financieros proporciona servicios, a cambio de un precio que reconoce la reposición de los recursos empleados, obteniendo así los objetivos anhelados por el empleador para el buen desarrollo de las actividades dentro de la empresa. El trabajador social ejerce varias funciones, entre las principales podemos destacar el diagnóstico, la planificación, orientación y el asesoramiento al trabajador en las condiciones laborales y recursos humanos, garantizando que los derechos no sean vulnerados, adquiriendo bienestar laboral individual o colectivo que es importante en una comunidad funcional o empresarial a la que pertenece, con una participación activa y motivadora de pertenecer a la empresa.
Keywords: ELEMENTO HUMANO; COMUNIDAD; POTENCIALIDAD; TRABAJO SOCIAL